Effectiveness of Mobile Learning: moPhyDict to Improve High School Students’ Physics Conceptual Understanding - Betti Ses Eka Polonia; Lia Yuliati (Universitas Lambung Mangkurat, 2019)
In learning physics, the problem that arises is a lack of physics conceptual understanding in contextual learning. These problems are due to the absence of innovative and creative learning resources that can be used to learn by the students. One of the learning resources that can be used is a dictionary. moPhyDict (mobile physics dictionary) is a dictionary containing explanations of concepts and illustrations (images, videos, animations) in a language that is easily understood by students. This study specifically aims to test the effectiveness of Mobile Learning: moPhyDict to improve student’s physics conceptual understanding. The method employed in this study was a quasi-experiment design. The experimental design used a pretest-posttest control group design. The sample of the study was 60 students from senior High School, which divided into control group and experiment group. The instrument test in this study used conceptual multiple choice question. Based on the t-test on the control class and the experimental class, it can be inferred that there is a significance score of 0.031. These results are supported by data: (1) the average score of the ability to understand the concept of the control class who did not use moPhyDict increased from 37.4 to 55.46, and (2) the average score of the conceptual understanding of the experimental class who used moPhyDict increased from 40.87 to 74.33. It was concluded that moPhyDict is effective to improve physics conceptual understanding of High School Students.